Diversity analysis of chickpea (Cicer arietinum) cultivars using STMS markers - BHARADWAJ, C; CHAUHAN, S K; RAJGURU, GAYATRI; SRIVASTAVA, RACHANA; SATYAVATHI, C TARA; YADAV, SHUBHA; RIZVI, AQEEL HASAN; KUMAR, J; SOLANKI, R K (The Indian Journal of Agricultural Sciences, 2010)
STMS primer pairs could clearly dissect the genetic diversity and relationship of chickpea (Cicer arietinum L.) varieties. Out of 55 STMS primer pairs, 35 generated polymorphism with an average 2.49 amplicons/primer pair. Polymorphic information content ranged from 0.48 to 1.0 and genetic similarity between cultivars ranged from 0.10 to 0.77. Dendrogram constructed based on UPGMA and bootstrapping of the data showed 2 distinct clusters with 2 subclusters. The grouping was on the basis of the ancestry. Association of sub-clustering appears to follow ancestry, seed type and flower colour which is supported by high boot strap values. It highlights the urgency for effective supplementation of pedigree data and other morphological data with the database generated by STMS marker to efficiently unearth the genetic inter-relationship among the genotypes as well as finger print the varieties for their protection. A high rate of polymorphism and occurrence of unique alleles or rare STMS alleles provides an immense opportunity for generation of comprehensive fingerprint database.